Hazard assessment of compound drought and heat events on summer maize from agricultural and meteorological perspectives - Qing Li; Peijuan Wang; Yang Li; Junxian Tang; Xin Li; Yuanda Zhang; Dianchen Han; Qi Wang; Yuncheng Zhao; Zaiqiang Yang (Agricultural Water Management)
Hazard assessment serves as the foundation for agricultural climate disaster risk assessment. As the impact of compound drought and heat events on agricultural production continues to intensity, this study constructed a hazard assessment model using a compound magnitude index improved by pre-factors and joint probabilities fitted with optimal copula functions. The aim was to compare and analyze the evolution characteristics and hazards of compound meteorological drought and heat events (CMDHEs) and compound agricultural drought and heat events (CADHEs) during different growth stages of summer maize. The results show that, across different growth stages of summer maize, SPRI and STCI, as well as SPI and STCI, exhibit negative correlations in different decades, with a stronger negative correlation between SPRI and STCI during the tasseling to maturity stage from 2011 to 2023. The pre-effect of meteorological drought in CMDHEs is higher than that of agricultural drought and heat in CADHEs. Our study also revealed a significant upward trend in CADHEs and CMDHEs since 2013 and 2017 during the tasseling to flowering stage. From sowing to tasseling, the hazard levels of CADHEs and CMDHEs were higher in the central and southern parts of Hebei Province and most regions of Henan Province. Compared to CMDHEs, CADHEs exhibit higher frequency and greater hazards across different growth stages of summer maize. These findings provide valuable insights for disaster prevention and mitigation of summer maize in the Huang-Huai-Hai Plain of China, ensuring food security and agricultural production.